Tramadol Alleviates Myocardial Injury Induced by Acute Hindlimb Ischemia Reperfusion in Rats - Takhtfooladi,Hamed Ashrafzadeh (2015)
Abstract Background: Organ injury occurs not only during periods of ischemia but also during reperfusion. It is known that ischemia reperfusion (IR) causes both remote organ and local injuries. Objective: This study evaluated the effects of tramadol on the heart as a remote organ after acute hindlimb IR. Methods: Thirty healthy mature male Wistar rats were allocated randomly into three groups: Group I (sham), Group II (IR), and Group III (IR + tramadol). Ischemia was induced in anesthetized rats by left femoral artery clamping for 3 h, followed by 3 h of reperfusion. Tramadol (20 mg/kg, intravenous) was administered immediately prior to reperfusion. At the end of the reperfusion, animals were euthanized, and hearts were harvested for histological and biochemical examination. Results: The levels of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were higher in Groups I and III than those in Group II (p < 0.05). In comparison with other groups, tissue malondialdehyde (MDA) levels in Group II were significantly increased (p < 0.05), and this increase was prevented by tramadol. Histopathological changes, including microscopic bleeding, edema, neutrophil infiltration, and necrosis, were scored. The total injuryscore in Group III was significantly decreased (p < 0.05) compared with Group II. Conclusion: From the histological and biochemical perspectives, treatment with tramadol alleviated the myocardial injuries induced by skeletal muscle IR in this experimental model.